Đặc điểm sinh khí hậu miền Nam Việt Nam qua phân tích các biểu đồ khí hậu - Vân, Nguyễn Khanh; Hiền, Nguyễn Thị; Lộc, Phan Kế; Hiệp, Nguyễn Tiến (Vietnam Journal of Earth Sciences, 2001)
Some features of bioclimatic conditions in South Vietnam Region based on analyzing of bioclimatic diagrams